Оценка сущности коэффициента финансовой независимости предприятия - Курденко, А. В. (ХНУРЭ, 2015)
The proposed material is considered a situation in which you need to analyze the financial independence of the company, relying only on the data sheet and total values of certain financial ratios. This situation may occur when analyzing audit activities of a firm (a competitor, partner). It is also an approach to the analysis of financial stability and solvency of the company, provided that the only known factor value financial independence and a total balance.
Keywords: финансовая независимость предприятия; коэффициент финансовой независимости